2007
DOI: 10.1186/1471-2474-8-89
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different skin-ankle brace application pressures on quiet single-limb balance and electromyographic activation onset of lower limb muscles

Abstract: Background: Several studies have been carried out in order to investigate the effect of ankle bracing on ankle joint function and performance. However, no study so far has examined the role of skin-brace interface pressure in neuromuscular control. The aim of this study was to investigate the effect of different skin-ankle brace interface pressures on quiet single limb balance and the electromyographic (EMG) activation sequence of four lower limb muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Following these promising findings, a number of research programmes have since examined the utility of different approaches for achieving improved performance outcomes, ostensibly via similar mechanisms. Such interventions have included: tapes [1921], braces [2224] and compression garments [2527] in young, healthy adults and people with lower-limb injuries (e.g., Functional Ankle Instability (FAI)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following these promising findings, a number of research programmes have since examined the utility of different approaches for achieving improved performance outcomes, ostensibly via similar mechanisms. Such interventions have included: tapes [1921], braces [2224] and compression garments [2527] in young, healthy adults and people with lower-limb injuries (e.g., Functional Ankle Instability (FAI)).…”
Section: Introductionmentioning
confidence: 99%
“…For young athletes with lower extremity injuries, studies have shown that compression via orthoses and sleeves improved uni- and bipedal balance performance [25,2931] and proprioception [14, 20]. However, Papadapoulos et al [24] suggested that ankle braces with 30kPa and 60kPa pressure were not able to alter the balance control strategy of the central nervous system (CNS). In an elderly sample, localized compression on the ankle was shown to improve joint position sense, but not a static balance performance [26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bernhardt and Anderson [4] reported that wearing compression shorts did not enhance joint position sense in young adults. Furthermore, Papadapoulos et al [24] suggested that ankle braces with 30 kPa and 60 kPa pressure were not able to alter the balance control strategy of the central nervous system (CNS). In an elderly sample, localized compression on the ankle was shown to improve joint position sense, but not static balance performance [16].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the taped feet were able to estimate the inclination better than when they were untaped. However, other studies [13,14] did not support the effect of taping improving functional foot stability as it was reported that taping did not improve balance ability [13,14] and muscular activation in the foot and ankle during one legged stance tests [14].…”
Section: Effects Of Tapingmentioning
confidence: 95%